Caribbean bananas : the macroeconomic impact of trade preference erosion - Mlachila, Montfort (IMF [Washington]US, 2010)
Examines the macroeconomic effects of the erosion of trade preferences, with a focus on the export of Caribbean bananas to Europe. Estimates the magnitude of implict assistance provided over a period of three decades to the Eastern Caribbean countries.